Práxis docente: desafios e possibilidades para uma formação multicentrada na aprendizagem - Almeida, Maria Cristina Silva Pereira (Universidade do Vale do Rio dos Sinos, 2018)
This arcticle proposes to promote reflections and foment a desire for a continuing education and the search of reflective teaching practice as a support that offer advances in professional performance of the teacher, facing the huge challenges that appear in the contemporary educational range. It happens because increasingly, it has been required from the teaching professionals, essential skills to improve their practices, know and understand the society and contemporary education needings. It concerns to this professional to search for innovative ways to develop a pedagogical conscious and humanized practice, focused on individual development and his/her integral learning. This work understands as relevant that the teacher must develop a practice that reverberate positively in the evolution of the students learning proccess, so it proposes as a theme "PráxisDocente": challenges and possibilities to a multicentered formation on learning. For this research, essentialy of bibliographic nature, it was made through published studies and surveys about the theme, collecting information, aspects and proposals about pedagogical práxis, with the intention of recognize as a functional strategy to educational formation and to the development of process of a meaningful learning of the students. .The study of the thematic chosen was developed from the analysis of dissertations, articles, titles published in the 80's, 90's and more recent productions produced by theoreticians, doctors in the area of education, sociology, psychology such as Lino de Macedo, Philippe Perrenoud, Maurice Tardiff, among others - essential references for the foundation of this research.From the present survey, we understand that choosing reflection and analysis about his/her practice the teacher will be able to support the applicability of pedagogical resources as effective diagnostic strategy, intervention, feedback, aiming the excellence status of the teaching-learning process.
Keywords: Prática pedagógica reflexiva; Formação continuada; Aprendizagem significativa; Reflective pedagogical practice; Continuing education; Meaningful learning